Āftāb-i Dakan : Qāʼid-i Millat Navvāb Bahādur Yār Jang kī savāniḥ ḥayāt - Shaidā, Ḥamīdullāh Ḵẖāṉ (SAMP early 20th-century Indian books project, 1944)
Biography of Bahādur Yār Jang, 1905-1944, Indian statesman from Hyderabad (Princely State)